Reliability Analysis and Economic Life Calculation for Asset Management Optimization (Case Study in Steam Power Generation Unit at XYZCompany) - Anugrah, Gede Bayu; Suef, Mokhamad (Institut Teknologi Sepuluh Nopember, 2020)
In a competitive market driven industry at a power generation business, requires The electricity producers to provide electricity with a low cost of supply. On the other hand, the large number of equipment assets managed by the power plant companies requires an appropriate asset management process, in order to reduce the increased maintenance and investment costs of equipment which which can cause an increase in the cost of supply. XYZ Company as a company that manages assets of more than Rp 174 trillion has challenges in the process of optimizing its company's asset management. The decreasing amount of maintenance and investment budget in the company each year and the equipment conditions that have been operated for more than 20 years, requires an asset management method that can provide a comprehensive understanding of the technical and economic conditions of each equipment, so it can be provide appropriate information to support the decision making process that is expected to reduce cost of supply.In this study, the authors conducted an analysis of asset conditions at XYZ Company by combining the method of reliability analysis and calculation of the economic life of the equipment. Case study was conducted at one of the units at XYZ Company precisely in Steam Turbine Unit 2.0. The purpose of this study is to obtain comprehensive information including the value of reliability and economic life of each equipment in the unit to facilitate management in the decision making process for the selection of maintenance strategies and asset replacement.Reliability analyzes were performed using RBD, RGA, and Weibull software. Reliability calculation will be done by looking at the amount and time between damages. Economic life calculation is done by calculating the annual equivalent cost. The analysis was performed on each equipment in the Steam Turbine Unit 2.0. From this analysis, it’s resulted the procedure for the classification of power plant equipment for the replacement process in accordance with the limits of the parameters of the reliability index and economic lifereliability and economic life conditon. Moreover, It’s resulted the mapping of Steam Turbine critical quipment. This mapping illustrates the amount of equipment that must be replaced immediately, still maintained, and the maintenance strategy needs to be evaluated immediately. This information is used by management in deciding the evaluation of equipment maintenance strategies and replacement strategies to reduce the power plant cost of supply.